1999
DOI: 10.1076/ceyr.18.4.249.5361
|View full text |Cite
|
Sign up to set email alerts
|

Effects of irrigation fluid temperature on choroidal circulation during vitrectomy

Abstract: The choroid acts as a thermostat to minimize intraocular temperature fluctuations by changing its blood flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…Our work in chicks with myopia-inducing goggles and ophthalmic nerve cuts, for example, suggests that the sensory input to the choroid may be involved in temperature-dependent regulation of ChBF (Shih et al, 1999). Consistent with the idea that ChBF can respond to temperature, ChBF in rabbits has been reported to increase with retinal cooling below or heating above 34 °C, and thereby maintain constant retinal temperature with ambient temperatures ranging from 30 to 40 °C (Tamai et al, 1999). Similarly, Stiehl et al (1986) showed that retinal temperature remains relatively constant during cooling of the conjunctiva in cats by up to 6 °C.…”
Section: Trigeminal Sensory Input To Choroidsupporting
confidence: 53%
See 1 more Smart Citation
“…Our work in chicks with myopia-inducing goggles and ophthalmic nerve cuts, for example, suggests that the sensory input to the choroid may be involved in temperature-dependent regulation of ChBF (Shih et al, 1999). Consistent with the idea that ChBF can respond to temperature, ChBF in rabbits has been reported to increase with retinal cooling below or heating above 34 °C, and thereby maintain constant retinal temperature with ambient temperatures ranging from 30 to 40 °C (Tamai et al, 1999). Similarly, Stiehl et al (1986) showed that retinal temperature remains relatively constant during cooling of the conjunctiva in cats by up to 6 °C.…”
Section: Trigeminal Sensory Input To Choroidsupporting
confidence: 53%
“…For example, reduced ocular blood flow caused by elevated IOP has been shown to result in reduced scleral and retinal temperature (Auker et al, 1982; Bill et al, 1983). Moreover, heating an eye in which blood flow has been reduced by elevation of IOP (which reduces ocular perfusion pressure and ChBF) results in an exaggerated rise in ocular temperature compared to eyes at normal IOP, suggesting that ChBF can play a role in thermoregulatory ocular cooling as well (Bill et al, 1983), as indicated also by Tamai et al (1999). ChBF-dependent thermoregulation may be important for retinal homeostasis and function (Parver et al, 1980).…”
Section: Trigeminal Sensory Input To Choroidmentioning
confidence: 99%
“…Indeed, our results show that Trpm8 −/− mice exhibit a higher drop in Teye than controls when exposed to mild cold. Consistent with our findings, a previous study revealed that temperature in the vitreous chamber above or below 34°C induces an increase in choroidal blood flow (ChBF), and only when intraocular temperature falls below 16°C, the ChBF decreases 42 . We therefore propose that mild drops of temperature inside the eye would be detected by TRPM8 channels in the sensory trigeminal fibres innervating choroidal vasculature, which will produce an increase in ChBF to maintain the intraocular temperature.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our findings, a previous study revealed that temperature in the vitreous chamber above or below 34°C induces an increase in choroidal blood flow (ChBF), and only when intraocular temperature falls below 16°C, the ChBF decreases. 42 We therefore propose that mild drops of temperature inside the eye would be detected by TRPM8 channels in the sensory trigeminal fibres innervating choroidal vasculature, which will produce an increase in ChBF to maintain the intraocular temperature. Whether vasodilation is mediated by F I G U R E 7 Liver and gonadal WAT are innervated by TRPM8-positive sensory fibre and TRPM8 regulates peripheral clocks in these tissues.…”
Section: Trpm8 Regulates Clockwork In Liver and Fatmentioning
confidence: 99%